Using the RSM to evaluate the rheological behavior of SiO2 (60%) - MWCNT (40%)/SAE40 oil hybrid nanofluid and investigating the effect of different parameters on the viscosity. (June 2023) - Esfe, Mohammad Hemmat; Tamrabad, Seyed Naser Hosseini; Hatami, Hossein; Alidoust, Soheyl; Toghraie, Davood
Abstract: The present study predicts dynamic viscosity of SiO2 (60%) - MWCNT (40%) hybrid nanofluid (HNF) in SAE40 oil as base fluid (BF) by comparing various models of RSM. This study was conducted under laboratory conditions with solid volume fractions of SVF= 0–1%, temperature of T = 25–50 °C and shear rates of SR= 666.5–9331 s −1 . Different models were used for this study, including 2FI, Quadratic, Cubic and Quartic models. These models were evaluated based on a series of quality indicators and charts. The indicators that were investigated in this study include standard deviation, coefficient of determination, P-value, correlation deviation (C.D) and coefficient of variation. After checking the quality indicators and charts for different models, the Quartic model was selected as the optimal model. In this study, the correlation functions of various models were used to determine the viscosity of HNFs. Then, according to the evaluation of the models, the Quartic model has been selected as the optimal model. The correlation function presented for the Quartic model has an acceptable accuracy in predicting the viscosity values of HNFs compared to the experimental data. Also, due to the dependence of viscosity on SR, the behavior of HNF is non-Newtonian. The values of standard deviation, coefficient of determination, P-value, correlation deviation, and coefficient of variation for the selected model were 6.67, 0.9960, 1.548584974e-218, − 4. 760 <C.D< 8.551 and 3.48, respectively. Next, the viscosity of HNF was optimized for the selected model in cold environmental conditions. The best state of viscosity of HNF in the cold environment in the conditions of SVF= 0, T = 31.958 °C and SR= 666.500 s −1 was 216.978 mPa.sec. Next, the different parameters effect on the viscosity of HNF was investigated and it has been determined that the temperature and SR parameters have the greatest and least effect on the viscosity of HNF, respectively. The findings can help to better understanding of rheological behavior of HNF and SAE40 engine oil in cold environmental conditions. By using the correlation function provided in the selected model, the viscosity of HNF can be calculated at any temperature, SVF and SR. This saves time and money and helps a lot to the industries that use this HNF and SAE40 engine oil. Highlights: The present study uses RSM to predict nanofluid properties. Rheological behavior of SiO2 (60%)-MWCNT (40%)/SAE40 HNF was analyzed. Models were used including 2FI, Quadratic, Cubic and Quartic models. Quartic model was selected as the optimal model. Best HNF viscosity in cold environment at SVF= 0, T = 31.958 °C and SR= 666.500 s −1 was 216.978 mPa.sec.